Regulatory Role of PBAN in Sex Pheromone Biosynthesis of Heliothine Moths - Jurenka, Russell; Rafaeli, Ada (Frontiers in Endocrinology, 2011)
Both males and females of heliothine moths utilize sex pheromones during the mating process. Females produce and release a sex pheromone for the long-range attraction of males for mating. Production of sex pheromone in females is controlled by the peptide hormone PBAN (pheromone biosynthesis activating neuropeptide). This review will highlight what is known about the role PBAN plays in controlling pheromone production in female moths. Male moths produce compounds associated with a hair-pencil structure associated with the aedaegus that are used as short-range aphrodisiacs during the mating process. We will discuss the role that PBAN plays in regulating male production of hair-pencil pheromones.